Editorial - Editor (PINS-Psychology in Society, 2025)
This issue, put together by the Cape Town editorial group picks up, in each of the contributions, themes which have been aired in earlier numbers of Psychology in Society, providing a picture of some continuity in areas of discussion for those concerned with a progressive view of psychology. If there is a common theme in the papers constituting Issue No 11 then it is to be found in a perspective of conceptual unravelling. Most of the papers are concerned with attempting to think more clearly about the terms and concepts which have already emerged as cornerstones of a more critical and socially concerned psychology in South Africa.